Self-compacting concrete with recycled aggregates - A literature review - Santos, S. (2019)
This paper presents a complete and updated literature review on the properties of self-compacting concrete with fine and coarse recycled aggregates. The subject of self-compacting concrete with recycled aggregates (RASCC) is greatly relevant to Society, since there is an increasing demand from the construction industry to adopt new processes to minimize its negative impacts on the environment. The use of recycled aggregates in concrete production presents a great environmental benefit through savings from the extraction of natural aggregates and the reduction of dumped material. The advantages associated to the use of both concrete with recycled aggregates and self-compacting concrete have boosted an increase in research and a consequent publication of literature in the last few years. Combining these two themes has allowed allying the environmental and economic advantages of each of the materials, leading to an innovative material of great interest to the construction industry in general. Even though RASCC is a relatively recent scientific area, studies on this material have demonstrated its viability, to produce both traditional and non-complex structural elements and highly complex and densely reinforced elements, which hinder the vibration procedures and may influence the final quality.